Dinamik Hubungan Diplomatik Türkiye-Israel: Kajian Retrospektif dari Tahun 1949 hingga 2002: The Dynamics of Türkiye-Israel Diplomatic Relations: A Retrospective Study from 1949 to 2002 - Nor Hidayah, Nur Syahirah; Mohd Nor, Mohd Roslan; Mohd Bakri, Mohamad Fikri; Madihah, Azka (Jurnal Usuluddin, 2025)
This article analyzes the diplomatic relationship between Türkiye and Israel from 1949 to 2002 within the context of Türkiye’s foreign policy transformation following the fall of the Ottoman Caliphate, as well as the influence of regional and global geopolitical forces. Türkiye’s official recognition of Israel in 1949 marked the beginning of a complex bilateral relationship, shaped by the legacy of secularism introduced by Mustafa Kemal Atatürk and Türkiye’s strategic alignment with the Western bloc during the Cold War era. Adopting a retrospective approach, the study examines how the legacy of the 1916 Sykes-Picot Agreement and broader imperial strategies that dismantled Islamic political institutions influenced Türkiye’s foreign policy narrative, particularly in relation to the Palestinian issue. Using historical and political analysis, this article traces patterns of diplomatic, military, and economic cooperation between the two nations, as well as the tensions arising from the protracted Palestinian-Israeli conflict. The findings reveal that although Türkiye–Israel relations have developed within a framework of pragmatic cooperation, they remain deeply affected by historical memory, domestic pressures, and Türkiye’s aspirations to restore regional Islamic solidarity. This study makes a significant contribution to understanding the dynamics of Türkiye’s foreign policy and its position within the postmodern geopolitical landscape of the Middle East.